Sensory characteristics and putrefaction test of broiler chicken meat dipping in Syzygium polyanthum infusion with different storage time - Suryanto, E; Jamhari, Jamhari; Afidah, U; Utami, N A (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4425, 2021)
This study aims at evaluating the sensory characteristics and putrefaction testing of broiler chicken meat dipping in Syzygium polyanthum infusion with different storage time. Observations were made on sensory quality of raw meat (color and aroma), cooked meat (color, aroma, flavor, and tenderness), and putrefaction testing of the eber test. The study considered two treatments, namely Syzygium polyanthum infuse concentrations (0 vs. 15%) during 30 minutes and different storage times at 4°C (0, 2, 4, 6, and 8 days) where each treatment repeated three times. The sensory characteristics test of chicken meat is performed by the panelist method. The collected data were analyzed by analysis of non-parametric with the Kruskal Wallis test. The results of the rot test were analyzed descriptively qualitatively. Data showed that the concentration of Syzygium polyanthum infusion and storage time could reduce the color and improve the aroma of raw meat and also tenderness and the smell of cooked meat. The initial rot of control chicken meat and bay leaf on day 4 with positive parameters used the Postma test and control chicken meat using the H 2 S test.